2015
DOI: 10.3855/jidc.6460
|View full text |Cite
|
Sign up to set email alerts
|

Application of Luminex Gastrointestinal Pathogen Panel to human stool samples from Côte d’Ivoire

Abstract: Introduction: Gastrointestinal infections caused by viruses, bacteria, and parasites are endemic in most developing countries due to inadequate provision of safe water supplies, sanitation, and hygiene. To investigate the enteric pathogens infecting people living in Côte d'Ivoire, the Luminex Gastrointestinal Pathogen Panel (xTAG GPP) assay was used to analyze 34 human fecal samples. This study represents the first application of this technology to samples from a sub-Saharan African country. Methodology: Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…positive samples were screened for the presence of common pathogens. The total nucleic acids were extracted as previously described [26]. For each specimen, the molecular diagnostic xTAG GPP Luminex assay (Luminex Molecular Diagnostics, Toronto, Canada), including adenovirus types 40/41, norovirus genogroup I and II (GI/GII), group A rotavirus, Campylobacter spp ., Clostridium difficile toxin A/B, Escherichia coli O157, enterotoxigenic Escherichia coli (ETEC) LT/ST, Salmonella spp ., Shiga-like toxin producing E .…”
Section: Methodsmentioning
confidence: 99%
“…positive samples were screened for the presence of common pathogens. The total nucleic acids were extracted as previously described [26]. For each specimen, the molecular diagnostic xTAG GPP Luminex assay (Luminex Molecular Diagnostics, Toronto, Canada), including adenovirus types 40/41, norovirus genogroup I and II (GI/GII), group A rotavirus, Campylobacter spp ., Clostridium difficile toxin A/B, Escherichia coli O157, enterotoxigenic Escherichia coli (ETEC) LT/ST, Salmonella spp ., Shiga-like toxin producing E .…”
Section: Methodsmentioning
confidence: 99%
“…Countries are identified by two-letter International Organization for Standardization (ISO) codes, and the study references are indicated in brackets. AO, Angola [23]; BD, Bangladesh [28,29,37,38,39]; BO, Bolivia [40]; BT, Bhutan [41,42]; BF, Burkina Faso [20,27,43]; CI, Cote d’Ivoire [44]; CM, Cameroon [26]; KH, Cambodia [45]; EG, Egypt [46]; ET, Ethiopia [47,48]; GE, Georgia* [49]; GH, Ghana [50,51]; IN, India [52,53,54,55,56,57,58,59,60,61,62,63,64,65]; ID, Indonesia [66,67]; KE, Kenya [68]; MG, Madagascar [69]; MA, Morocco [70,71]; MW, Malawi [72,73]; MD, Republic of Moldova* [49]; NP, Nepal [22,74]; NG, Nigeria [75,76]; NI, Nicaragua [21,77]; PG, Papua New Guinea [78]; PK, Pakistan [79,80]; RW, Rwanda [81]; SD, Sudan [82]; TZ, Tanzania [83,84,85]; TN, Tunisia [86,87,88]; UA, Ukraine...…”
Section: Figurementioning
confidence: 99%
“…There is a growing concern of asymptomatic colonization of enteropathogens in the gut of the children in the endemic countries because of its impact on longitudinal public health issues, such as growth faltering, oral vaccine low efficacy and poor neurocognitive development through environmental enteropathy/environmental enteric dysfunction [ 24 ]. Asymptomatic ETEC infections are common in endemic countries and may impact the intestinal health as well as long-term developmental potential in the children in these areas [ 4 , 25 ]. This low dose CHIM model of ETEC may serve as a tool to decipher these critical interactions.…”
Section: Discussionmentioning
confidence: 99%